The impact of modified fluid gelatin 4% in a balanced electrolyte solution on plasma osmolality in children—A noninterventional observational study. Issue 8 (31st May 2022) - Rudolf, Daniel; Witt, Lars; Boethig, Dietmar; Rigterink, Vanessa; Zander, Rolf; Sümpelmann, Robert; Dennhardt, Nils
Abstract: Background: Intravenous fluids for perioperative infusion therapy should be isotonic to maintain the body fluid homeostasis in children. Modified fluid gelatin 4% in a balanced electrolyte solution has a theoretical osmolarity of 284 mosmol L −1, and a real osmolality of 264 mosmol kg H2 O −1 . Because both values are lower than those of 0.9% saline or plasma, gelatin would be expected to be hypotonic in‐vitro and in‐vivo. Aim: We thus hypothesized that the infusion of gelatin would be expected to decrease plasma osmolality. We performed an in‐vitro experiment and an in‐vivo study to evaluate the impact of gelatin on the osmolality in children. Methods: In the in‐vitro experiment, full blood samples were diluted with gelatin 4% or albumin (50 g L −1 ) from 0% (pure blood) to 100% (pure colloid), and the osmolality was measured by freezing‐point depression. In the in‐vivo study, blood gas analyses from children undergoing major pediatric surgery were collected before and after gelatin infusion, and the osmolality was calculated by a modified version of Zander's formula. Results: In the in‐vitro experiment, 65 gradually diluted blood samples from five volunteers (age 25–55 years) were analyzed. The dilution with gelatin caused no significant changes in osmolality between 0% and 100%. Compared with gelatin, the osmolality in the albumin group was significantly lower between 50% and 100% dilution ( p  < .05). In the in‐vivo study, 221 children (age 21.4 ± 30 months) were included. After gelatin infusion, the osmolality increased significantly (mean change 4.3 ± 4.8 [95% CI 3.7–4.9] mosmol kg H2 O −1 ; p  < .01) within a normal range. Conclusions: Gelatin in a balanced electrolyte solution has isotonic characteristics in‐vitro and in‐vivo, despite the low theoretical osmolarity, probably caused by the (unmeasured) negative charges in the gelatin molecules contributing to the plasma osmolality. For a better evaluation of the (real) tonicity of gelatin‐containing solutions, we suggest to calculate the osmolality (mosmol kg H2 O −1 ) using Zander's formula. Trial registration: ClinicalTrials.gov (ID: NCT02495285).